2018
DOI: 10.1186/s13256-018-1780-2
|View full text |Cite
|
Sign up to set email alerts
|

Successful treatment of out-of-hospital cardiopulmonary arrest due to streptococcal toxic shock syndrome – effectiveness of extracorporeal membrane oxygenation and the rapid antigen group A streptococcus test: a case report

Abstract: BackgroundStreptococcal toxic shock syndrome caused by Streptococcus pyogenes, a group A streptococcus, infection is a rare condition that rapidly progresses to multiple organ failure, shock, and death. It is thus important to promptly establish a diagnosis, provide hemodynamic support, and initiate appropriate antibiotics therapy.Case presentationA 70-year-old Asian man presented with ventricular fibrillation. Extracorporeal membrane oxygenation was initiated 20 minutes after admission after unsuccessful conv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 9 publications
0
6
0
2
Order By: Relevance
“…A total of 7 case reports describing 8 patients [7–13] and 1 retrospective observational study describing 10 patients [15] were identified. In addition, 1 case report was manually searched.…”
Section: Discussionmentioning
confidence: 99%
“…A total of 7 case reports describing 8 patients [7–13] and 1 retrospective observational study describing 10 patients [15] were identified. In addition, 1 case report was manually searched.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, mNGS is not the only tool for rapid detection. It was reported that an optical immunoassay technology that could detect the GAS antigen within 5–10 min was available ( 29 ). Another two rapid molecular tests targeting the speB gene of GAS are used experimentally, one of which could get the result in approximately 25 min ( 30 ).…”
Section: Discussionmentioning
confidence: 99%
“…110,111 Despite these challenges, there are many clinical cases in which patients placed on ECMO after CA are able to leave the hospital with full neurological recovery. 112,113 Although not perfect, ECMO provides the potential for life for selected candidates after CA. 108,111,114,115 Beginning in the late part of the last century, many preclinical studies assessed the beneficial effects of cooling the body and the brain after CA.…”
Section: Education and Teamworkmentioning
confidence: 99%